Steady RANS Assessment of Stall Fence Effects on Wells Turbine Performance for Oscillating Water Column Systems - Muhammad Nurfajriansyah Muslich; Aditya Rio Prabowo; Ristiyanto Adiputra; Seung Jun Baek; Svitlana Onyshchenko; Mahfud Alfajar; Dominicus Danardono Dwi Prija Tjahjana; Iwan Istanto; Rahman Wijaya; Hermes Carvalho (Institute of Multidisciplinary Research and Community Service, 2026)
The Wells turbine is a key component in an Oscillating Water Column (OWC)-based ocean wave energy conversion system, yet its limited operating range due to leading-edge stall constrains overall system efficiency. This study presents an independent CFD benchmark of the performance of the Wells turbine with and without a passive flow control device, a stall fence, as investigated by Das and Samad (2020). Steady Reynolds-Averaged Navier-Stokes (RANS) simulations using the SST k-ω turbulence model were performed in ANSYS CFX v22.1 by replicating the original geometry, boundary conditions, and mesh density for direct comparison. The reference turbine (eight NACA 0015 blades, solidity 0.64) and the configuration with a stall fence (fences at 40% and 80% span) were evaluated over a flow coefficient range of φ = 0.075-0.275. Grid independence study using quantitative (non-dimensional torque T*) and qualitative (tip-vortex topology) criteria resulted in the selection of a 3.5-million-element mesh. For the reference turbine, a mean absolute percentage error (MAPE) of 2.0% for T* and 3.1% for efficiency was obtained in the pre-stall range (φ ≤ 0.225), confirming strong numerical reproducibility. However, steady RANS failed to predict the stall onset for the reference configurations and overpredicted torque by up to 508% in the post-stall region. The stall point at φ = 0.250 was successfully reproduced with a deviation approaching zero, proving that the vorticity induced by the fence geometry enhances the reliability of RANS stall predictions. The pre-stall MAPE for the fence configuration was 4.4% for T*, slightly higher due to local vortex interactions around the fence. These findings establish steady RANS as a reliable design tool in the pre-stall range and demonstrate that passive fence stalls not only extend the turbine’s operating range but also improve the accuracy of CFD predictions. Keywords: Wells turbine, Stall fence, CFD benchmark, Steady RANS, Ocean wave energy conversion.